Front Cover: Acetylation Rather than H50Q Mutation Impacts the Kinetics of Cu(II) Binding to α‐Synuclein (ChemPhysChem 23/2021). Issue 23 (3rd December 2021) - Teng, Xiangyu; Sheveleva, Alena; Tuna, Floriana; Willison, Keith R.; Ying, Liming
Abstract : The Front Cover shows that N‐terminal acetylation of α‐synuclein shifts the binding from the N‐terminus to His50 and significantly slows down the binding reaction. More information can be found in the Article by Liming Ying and co‐workers .